Aplikasi Danger Message Daerah Rawan Kecelakaan Dengan Android GIS - Ranu - Setyobudi; Matlubul Khairi; Sulistiyanto - - (Universitas Islam Lamongan, 2019)
There are several areas in Probolinggo District where accidents often occur because the location of the existing road is indeed very dangerous, because of sharp turns or because of the heavy traffic on the road, this problem can be reduced by giving messages through the Android mobile application. The number of accidents that occur in various places with the time of the incident in the district of Probolinggo can be obtained at the Office of Transportation. The purpose of this research is to create an GIS android application that can provide information about maps of accident-prone areas in Probolinggo Regency. The method used is using a spiral. With stages, Planning, Risk Analysis, Product Engineering, Evaluation by users. Information about traffic accident-prone locations is very much needed by the community, transportation department and law enforcement in this case the police. Android-based Geographic Information System as an appropriate tool to be applied in this case because it uses the Mapping location of accident-prone areas and will, sending messages (danger message), in the form of user distance from accident-prone locations.